Challenges for African science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Professor Thomas Odhiambo is Director of the International Centre of Insect Physiology and Ecology (ICIPE) in Kenya. Among other international awards, in 1987 he shared with President Abdou Diouf of Senegal the First Hunger Prize for the Sustainable...